Association between Loneliness, Mental Health Symptoms, and Treatment Use among Emerging Adults. Issue 2 (6th March 2023) - Bessaha, Melissa; Mushonga, Dawnsha; Fedina, Lisa; DeVylder, Jordan
Abstract: Loneliness research has focused primarily on older adult populations. There is limited research on how loneliness and social support impact young people's mental health and mental health services use. This article reports an assessment of whether loneliness and social support are associated with mental health services use and mental health symptoms (psychological distress and suicidal ideation) among emerging adults. A subsample of emerging adults ages 18 to 29 ( N = 307) was drawn from the 2017 Survey of Police-Public Encounters, a cross-sectional, general population survey administered to residents of New York City and Baltimore. Ordinary least squares and binary logistic regression analyses were performed to model associations between loneliness and mental health symptoms and services use outcomes. Emerging adults with higher levels of loneliness reported higher levels of distress and suicidal ideation. Having more social support, experiencing higher levels of distress, and suicidal ideation were associated with increased odds for using services. First-generation American emerging adults and Black emerging adults were less likely to use services than their U.S.-born and non-Black counterparts. The significant impact of loneliness on mental health symptoms and the effect of social support on service use highlight the importance of developing interventions to prevent and reduce loneliness over the life course.